Kingdom of Lesotho : Staff Report for the 2012 Article IV Consultation and Second and Third Reviews Under the Three-Year Arrangement Under the Extended Credit Facility and a Request for Augmentation of Access: Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of Lesotho. (IMF Staff Country Reports; Country Report ;, 2012)
This staff report examines the Kingdom of Lesotho's 2012 Article IV Consultation and second and third reviews under the three-year arrangement under the Extended Credit Facility. Real GDP growth for 2010/11 is estimated at 5 3/4 percent, and inflation rose gradually in 2011, driven by international commodity prices. Despite the sharp drop in Southern African Customs Union (SACU) revenues, fiscal performance in 2010/11 has been much better than programmed, reflecting higher domestic revenue collections and cuts in recurrent spending.